1998
DOI: 10.1016/s0142-9612(97)00218-4
|View full text |Cite
|
Sign up to set email alerts
|

Protein patterning

Abstract: The current technology available for patterning proteins is reviewed. Examples of two-dimensional protein patterning using conventional photolithographic methods, photochemistry, and self-assembled monolayers are given. Consideration is also given to some major issues affecting protein patterning, including non-specific binding, protein pattern uniformity, and measurement techniques. S-layer nanopatterning and three-dimensional biochip patterning are discussed in possible future directions. In addition, a disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
366
0
10

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 508 publications
(379 citation statements)
references
References 0 publications
0
366
0
10
Order By: Relevance
“…It is well established that the organization of the adsorbed protein layer (composition, quantities and conformation) depends on the physicochemical properties of the polymer surface [33,34]. The protein adsorption experiments showed that both PET (reference membrane) and PEI adsorbed the highest amount of FN (Fig.…”
Section: Protein Adsorptionmentioning
confidence: 92%
“…It is well established that the organization of the adsorbed protein layer (composition, quantities and conformation) depends on the physicochemical properties of the polymer surface [33,34]. The protein adsorption experiments showed that both PET (reference membrane) and PEI adsorbed the highest amount of FN (Fig.…”
Section: Protein Adsorptionmentioning
confidence: 92%
“…These compounds come in a variety of chemistries that are used for many applications and are often utilized to modulate the biological interactions of silica substrates with biological materials. 11 Work has shown that it is possible to pattern the aminated alkylsilane DETA using deep-ultraviolet ͑DUV͒ photolithography. [12][13][14][15][16] Using DUV, SAMs were exposed to intense ultraviolet light from an ArF excimer laser ͑emission wavelength 193 nm͒.…”
Section: Introductionmentioning
confidence: 99%
“…For in situ regeneration, a scaffold implanted directly into the injured tissue stimulates the body's own cells to promote local tissue repair [657,759]. In any case, simply trapping cells at the particular point on a surface is not enough: the cells must be encouraged to differentiate, which is impossible without the presence of suitable biochemical factors [760]. All previously mentioned clearly indicates that for the purposes of tissue engineering, calcium orthophosphate bioceramics plays an auxiliary role; namely, it acts as a suitable material to manufacture the appropriate 3D templates, substrates or scaffolds to be colonized by living cells before the successive implantation [761,762].…”
Section: Bioceramic Scaffolds From Calcium Orthophosphatesmentioning
confidence: 99%